Investigation of SOD2 Gene Polymorphism in the Patients with Type Two Diabetes Disease in Babylon Province - Zahraa Kamil Kadhim Lawi (Journal of Global Pharma Technology, 2018)
Diabetes is a defect with body of human that causes blood glucose (sugar) levels to increase higher than normal. This is also named hyperglycemia. The free radical theory of many illness that reactive oxygen species (ROS) participate a key function in accumulation of cellular damage, The results of PCR-SSCP for SOD2 gene illustrated that two different haplotypes according to the numbers of bands in the SOD2gene including 5 and 6 bands. While, these haplotype was detected between two groups; in diabetes patient groups and control, the results indicate that was association between 3 and 4 bands in patients as compared with a control group. the patients groups, had greater levels of SOD in contrast with control groups result at significant differences (P≤ 0.05). Conclusion PCR-SSCP Is a good screening method to detection SOD2 snps gene in patient with diabetes type 2 diseaseKeywords: Antioxidant, SOD2, Diabetes, Oxidative, SSCP, PCR.